Pengaruh Penambahan Karet Alam (Lateks) Pada Campuran Cold Paving Hot Mix Asbuton (Cphma) - Khaerah, Arinil; Nurdin, Abd Rahim; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Cold Paving Hot Mix Asbuton (CPHMA) Asbuton mixture consisting of aggregate, granular asphalt, rejuvenator and other added ingredients which are mixed hot cold paved. This product is an alternative that is very suitable for road construction in remote areas and small islands. where asphalt mixing plant (AMP) facilities are limited. The purpose of this study was to identify the effect of natural rubber (latex) on marshall characteristics in CPHMA mixtures. This study used the addition of natural rubber (latex) content of 10%, 15% and 20%. Samples were made of 15 briquettes consisting of 6 characteristic briquettes and 9 variation briquettes. The manufacture of briquettes refers to the Bina Marga General Specifications 2018. Sample testing is carried out using the marshall method. The test results show that the effect of adding natural rubber (latex) has no effect on the properties of the CPHMA mixture and causes the value of the mixture to decrease and natural rubber (latex) in any percentage does not affect the value of stability and durability.